2004
DOI: 10.1590/s0100-83582004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and growth of weeds under custard apple (Annona squamosa) progenies

Abstract: -Weeds have a negative influence on several fruit tree characteristicsKey words: Annona squamosa, custard apple fruit, weeds. RESUMO -As plantas daninhas (PD) afetam várias características das fruteiras, inclusive orendimento, e podem dificultar a execução de tratos culturais nos pomares. Existe interesse em métodos alternativos de manejo das PD, visando reduzir o uso de herbicidas, que são caros e causam degradação ambiental. Dentre esses métodos, a adoção de cultivares com maior habilidade competitiva com as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…The rootstock factor, determining the fruit tree crown size, had a much smaller influence on the level of weed infestation than the water conditions. The phenomenon of significant weed suppression under a large tree canopy, reported by Silva et al [22], was observed in the present study only in case of Epilobium adenocaulon and Trifolium repens. These two species became dominant late during the fruit-bearing period.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The rootstock factor, determining the fruit tree crown size, had a much smaller influence on the level of weed infestation than the water conditions. The phenomenon of significant weed suppression under a large tree canopy, reported by Silva et al [22], was observed in the present study only in case of Epilobium adenocaulon and Trifolium repens. These two species became dominant late during the fruit-bearing period.…”
Section: Discussioncontrasting
confidence: 50%
“…Some weed species can be present in the orchard only in certain vegetation periods, whereas other ones are observed every year and show a nearly constant frequency [18,19]. As the diameter of the tree canopy increases, the number of weeds found under the tree shrinks [22]. From the point of view of fruit production, it is important to determine the weed abundance levels beyond which particular weed species become harmful for the agricultural landscape [23].…”
Section: Introductionmentioning
confidence: 99%